A historical overview of the activation and porosity of metal-organic frameworks - Zhang, Xuan; Chen, Zhijie; Liu, Xinyao; Hanna, Sylvia L; Wang, Xingjie; Taheri-Ledari, Reza; Maleki, Ali; Li, Peng; Farha, Omar K (Chemical Society reviews, 2020)
Since the first reports of metal-organic frameworks (MOFs), this unique class of crystalline, porous materials has garnered increasing attention in a wide variety of applications such as gas storage and separation, catalysis, enzyme immobilization, drug delivery, water capture, and sensing. A fundamental feature of MOFs is their porosity which provides space on the micro- and meso-scale for confining and exposing their functionalities. Therefore, designing MOFs with high porosity and developing suitable activation methods for preserving and accessing their pore space have been a common theme in MOF research. Reticular chemistry allows for the facile design of MOFs from highly tunable metal nodes and organic linkers in order to realize different pore structures, topologies, and functionalities. With the hope of shedding light on future research endeavors in MOF porosity, it is worthwhile to examine the development of MOFs, with an emphasis on their porosity and how to properly access their pore space. In this review, we will provide an overview of the historic evolution of porosity and activation of MOFs, followed by a synopsis of the strategies to design and preserve permanent porosity in MOFs. A historical overview of the activation and porosity of MOFs including strategies to design and preserve permanent porosity in MOFs.